Accurate imaging of hydraulic fractures using templated electrical resistivity tomography. (September 2019) - Wu, Hui; Fu, Pengcheng; Yang, Xianjin; Morris, Joseph P.; Johnson, Timothy C.; Settgast, Randolph R.; Ryerson, Frederick J.
Highlights: A templated electrical resistivity tomography method to image hydraulic fractures. Maximize the use of a priori information to regularize inversion. Demonstrated efficacy with comprehensive sets of synthetic data. Abstract: Hydraulic fracturing has proven to be an essential technique for enhancing oil, gas and heat recovery from subsurface reservoirs. Accurate characterization of stimulated hydraulic fractures has significant scientific and practical value but remains practically challenging. We propose a novel templated electrical resistivity tomography (TERT) method to estimate both the extents and aperture of a hydraulic fracture through two key innovations. First, unlike the traditional ERT methods which image the perturbed electrical resistivity field, TERT images the perturbation to the smooth background field, where the perturbation is a planar feature caused by the hydraulic fracture in a 3D space. Second, we maximize the use of a priori information of the fracture and minimize the parameter space by using geometric templates to characterize the fracture. A hypothetical elliptical fracture in a 3D model as well as a field-scale hydraulic fracture corresponding to a typical reservoir stimulation scenario are successfully imaged with TERT.